Analysis of Factors that Influence Consumer Purchasing Decisions on the Shopee Marketplace and Comparison with Other Marketplaces - Hikmah Mardiana Shofa; Chika Meidyanputri; Zaizatun Rizka; Rusdi Hidayat; Indah Respati Kusumasari (Finance : International Journal of Management Finance, 2024)
This study aims to identify the factors influencing purchasing decisions on the Shopee marketplace and compare them with other marketplaces. The research employs a literature review method. The results show that Shopee excels in driving impulsive purchases through promotions and major events, while Lazada focuses on customer experience and transaction security. Meanwhile, Tokopedia relies on brand reputation and transaction safety. Each platform adopts its own approach, but all three emphasize building customer trust and attracting attention through relevant promotions.